Credit and land contracting: A test of the theory of sharecropping - Das, Narayan Chandra; Janvry, Alain de; Sadoulet, Elisabeth (Wiley Online Library, 2022)
This article was published in The American Journal of Agricultural Economics [©2019 Published by Agricultural and Applied Economics Association] and the definite version is available at: https://doi.org/10.1093/ajae/aaz005 The Article's website is at: https://onlinelibrary.wiley.com/doi/full/10.1093/ajae/aaz005